CSF biomarkers and blood pressure trajectories in normotensive individuals and subjects with controlled and uncontrolled hypertension. (31st December 2021) - Glodzik, Lidia; Butler, Tracy; Li, Yi; Tanzi, Emily; Harvey, Patrick; Blennow, Kaj; Zetterberg, Henrik; de Leon, Mony J.
Abstract: Background: Hypertension is a risk factor for Alzheimer's disease, however relationships between this disease and CSF amyloidβ42, total tau and phosphorylated tau (p‐181) are inconclusive. Even less is known about associations between trajectories of blood pressure and AD biomarkers. Method: Longitudinal CSF examinations were performed in 132 normotensive subjects (BP<140/90, and no antihypertensive treatment), 35 subject with controlled hypertension ((BP<140/90, and antihypertensive treatment), and 32 subjects with uncontrolled hypertension (BP≥140/90, irrespective of treatment), mean age 64.3 ± 9.3 years, 61% women. Biomarker changes over time, and relationship between changes in biomarkers and changes in systolic and diastolic blood pressure were tested using repeated measures mixed model. Result: Normotensive group was younger than 2 other groups, percentage of women did not differ. Baseline biomarkers levels were not different between groups. After a mean follow‐up time of 3.7±2.7 years total tau and p‐tau181 increased in the normotensive and uncontrolled groups, but did not change in the controlled group ( group*time : F=3.2, p=.04 and F=3.2, p=.04 for total tau and p‐tau181, respectively). Amyloidβ42 remained unchanged in the normotensive and controlled groups, but decreased in the uncontrolled group ( group*time : F=3.1, p=.04). Change in systolic blood pressure was inversely related to change in total tau only in the uncontrolled group ( group*time : F=5.0, p=.007). Change in diastolic blood pressure was inversely related to change in ptau‐181 tau only in the uncontrolled group ( group*time : F=4.2, p=.02). No other relationship between blood pressure and biomarkers was detected. Conclusion: Subjects with baseline uncontrolled hypertension experienced longitudinal changes in amyloid and tau markers most consistent with progression toward Alzheimer's disease. Interestingly, in this group increases in tau and p‐tau181 coincided with reduction in blood pressure. This may indicate relationship with relative hypoperfusion in subjects with vasculature compromised by years of high blood pressure.